Microplastics in sediments of the waters near the Akademik Vernadsky station - Nasiedkin, Yevhen; Olshtynska, Oleksandra; Ivanova, Ganna; Kadurin, Sergey (Ukrainian Antarctic Journal, 2025)
Despite Antarctica’s remoteness from powerful sources of anthropogenic impact, its natural environment undergoes changes due to the activities of scientific stations, tourism, transport communications, and the extraction of bioresources. The study presents the distribution of artificial polymer particles (microplastics) in the upper layer of the bottom sediments in the waters near the Akademik Vernadsky station. It aims to identify the microplastics in the geological components and to adapt the laboratory cycle of sample processing and particle identification. The samples were collected in 2022 during seasonal fieldwork at 4 to 60 m. In particular, sediment samples from sea straits at different distances from the Antarctic station were subject to testing. Most of the samples included microplastics; they were quantified and classified by morphology. The putative microplastics were tested by Raman spectroscopy (diffraction monochromator MDR-23); the test found such polymers as polypropylene, polyethylene, and polyethylene terephthalate. Some particles (mostly fibers) that morphologically could not be studied by spectrometry were identified as artificial polymers by thermal techniques without chemical analysis. The sediments’ material and granulometric parameters were determined to understand the possible link of the microplastics in the upper sedimental layer with the natural and anthropogenic factors. The results were compared to similar studies at other polar stations on the Antarctic Peninsula. The small number of samples did not allow us to establish a qualitative relation between the depth distribution, sediments’ granulometry, and the total amounts of the confirmed microplastic fragments. Thus, the publication should be considered a preliminary review and a methodologically indicative study on the identification of microplastic particles in the bottom sediments of the water area adjacent to the Ukrainian Antarctic Station.